2007
DOI: 10.1037/cp2007005
|View full text |Cite
|
Sign up to set email alerts
|

The assessment of credibility: An analysis of truth and deception in a multiethnic environment.

Abstract: Evidence-base practice (EBP) is now commonplace in many health care services and, in recent years, there has been a healthy debate about the role of EBP in psychology. In this article, I provide information on the nature of EBP and how it is consistent with professional training models and standards in psychology. In discussing some of the concerns that have been raised about the value of EBP in psychology, I present research fmdings on the relevance and potential impact of evidence-based assessment and treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…Despite the importance of credibility assessment in many contexts (e.g., criminal justice system), it is not a skill that has been mastered, and likely never will be (although there are some promising lines of research that may move us toward that goal, e.g., Vrij & Granhag, ). One area that has received little attention, but is becoming increasingly important, is the ability to detect deceit in people who are not speaking their first language (Sabourin, ). This skill is crucial for professionals in many settings, from clinicians detecting malingering to customs, immigration, and border patrol officials attempting to determine who can enter and exit the country, to law enforcement dealing with witnesses and suspects, and to military and human intelligence personnel attempting to gain information from sources and detainees overseas.…”
Section: Detecting Deception In Non‐native English Speakersmentioning
confidence: 99%
“…Despite the importance of credibility assessment in many contexts (e.g., criminal justice system), it is not a skill that has been mastered, and likely never will be (although there are some promising lines of research that may move us toward that goal, e.g., Vrij & Granhag, ). One area that has received little attention, but is becoming increasingly important, is the ability to detect deceit in people who are not speaking their first language (Sabourin, ). This skill is crucial for professionals in many settings, from clinicians detecting malingering to customs, immigration, and border patrol officials attempting to determine who can enter and exit the country, to law enforcement dealing with witnesses and suspects, and to military and human intelligence personnel attempting to gain information from sources and detainees overseas.…”
Section: Detecting Deception In Non‐native English Speakersmentioning
confidence: 99%
“…However, this chapter has challenged this view and argued that deception research needs to move away from this "cultural vacuum" perspective (Kim et al 2008, p. 24) and start recognizing the cultural and cross-cultural factors that may impact deceptive communication and lie detection in cross-cultural contexts. It was argued that this view is problematic because it largely ignores the influence of culture in the communication process, particularly given that contemporary research has shown that culture has a significant impact on the way an individual communicates and that deceptive communication is not exempt from such influence (e.g., Gudykunst 2004;Sabourin 2007;Vrij andWinkel 1991, 1994).…”
Section: Resultsmentioning
confidence: 99%
“…Deception is defined as the purposeful act of creating an impression in others, in spite of the deceiver's knowledge that the information provided is false, misleading or inaccurate (Zukerman, Depaulo, & Rosenthal, 1981). By this definition, individuals who provide inaccurate information during an investigation process-perhaps due to possible memory failures or while in states of psychological distress or highly suggestible states-cannot be classified as deceptive, even though they may be considered unreliable witnesses (Sabourin, 2007). Given the importance of assessments or judgments of truthfulness in criminal justice and security intelligence operations, as well as the complexity of rendering decisions of truth or deception, an understanding of the process and persons who render said assessments and factors leading to the correct judgments of truthfulness or deception is important.…”
Section: Personality Training and Detection Of Deceptionmentioning
confidence: 99%
“…This strategy accorded persons with good personal background and reputation more credibility than persons who were of ill repute. However, this reputation-centric assessment of credibility did not take into account that deception is a situation-specific behavior and that persons of good reputation in certain situations have the potential to engage in deception and provide false statements or testimony (Sabourin, 2007).…”
Section: Defining Credibilitymentioning
confidence: 99%